DETERMINATION OF KINETIC PARAMETERS FOR RIVER WATER QUALITY MODEL: A CASE STUDY IN THE UPPER ZONE OF CITARUM RIVER - Iskandar A. Yusuf (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2016)
Along with the development of urban and industrial areas, a lot of river contaminated by wastewater become heavily polluted river so it is necessary to control water pollution which is anticipated by water quality modeling. Researcher from Research Center for Water Resources conducts research to assess the magnitude of kinetic parameters for river water quality modeling in order to provide reference to the way the initial kinetic parameter estimation in order to facilitate the implementation of good calibration so that the model obtained approached the field conditions. Appraisal method to make reference to the way the the initial kinetic parameters in general: 1) based on various of exist references in the form of tables and or formulas, 2) by calculating the change in water quality between upstream and downstream sampling locations. For initial estimation of BOD decay coefisien beside two methodes appoiresaid, also water quality testing in particular calculation of laboratory test results of daily BOD for 12 days. Results from this research that provides the way to carry out a preliminary assesment of kinetic parameters in detail based on the conditions of river kinetic and hydraulic that give easy of the water quality model calibration. To give control restrictions have created a table minimum to maximum range value of several kinetic parameters and also presented a refference table and the range of values ever measured kinetic parameters in Indonesia to produce a good water quality models.